Mengupas Etnomatematika pada Bangunan Masjid Raya Tanjung Pauh Hilir Kerinci - Asdamayanti, Nurul; Yulianti, Putri; Rusliah, Nur; Anggraini, Reri Seprina (Square : Journal of Mathematics and Mathematics Education, 2024)
Mathematics with the nuances of ethnomathematics culture at this time its presence makes a major contribution to the learning of mathematics. This research was conducted to find the elements of mathematics in the building of the grand mosque which is located in Tanjung Pauh Hilir, West Lake Kerinci sub-district, Kerinci district, Jambi province. This study uses a qualitative method with an ethnographic approach. The data used are data obtained from observation, documentation and interviews. The results showed that the mathematical concepts in this mosque building contained geometrical materials such as ellipses, rhombuses, circles, semicircles, squares and rectangles while geometrical materials contained such as octagonal prisms, beams and pyramids and also transformations such as reflections. With the existence of ethnomathematics in this building it is hoped that it will be able to improve mathematical abilities, instill local wisdom values and also through observing mosque buildings in being able to explain that cultural elements can be used in learning mathematics.Keywords: Ethnomathematics, Building, Tanjung Pauh Grand Mosque.